Journal Motion Simulation of Hydrodynamic Journal Bearing Considering Elastic Effects - Singh, Harsh Vardhan (My University, 2008)
A journal bearing system, if disturbed from its equilibrium position, experiences change in the hydrodynamic forces acting on it. This disturbs the equilibrium of the journal and makes its centre to whirl around the static equilibrium position. The dynamic response of a journal bearing system under these conditions can be obtained using either linear or non-linear equation of motion of journal motion. The present work is aimed to determine the realistic dynamic response of hydrodynamic bearing. In this work, the nonlinearized dynamic response of the journal bearing for both rigid and flexible bearing is studied by considering two cases of journal mass with respect to critical mass obtained from linear analysis .i.e. = and > . The deviation in stability margins is established by comparing the results obtained from the linearized and nonlinearized stability analysis for elastohydrodynamic case. The coupled solution of Reynold’s equation and elasticity equation is obtained using finite element method and the equation of motion is computed using fourth order Runga-Kutta method. The results obtained in the present work for nonlinear dynamic analysis of hydrodynamic bearing shows an increase in stability margin as compared to linear analysis for a case when isothermal conditions are assumed and bearing is considered flexible.
M.E. CAD/CAM & Robotics
Keywords: Hydrodynamic Bearing; Journal Bearing; Journal Motion Simulation